Pengaruh Akhir Zaman terhadap Perilaku Moral - Martina Rosmaulina Marbun; Nur Asnayanti Buulolo; Yasozatulo Lase; Agnes Monika Sarumaha; Seiring Lahoho (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This paper discusses the concept of the influence of the end times on moral behavior. Eschatology is one of the important doctrines in Christian theology that not only discusses end-time events, such as the Second Coming of Christ, the resurrection of the dead, and the Last Judgment, but also has a real influence on the moral life of believers. This study aims to analyze how the understanding of the end times affects moral behavior in daily life. Awareness of the coming of Christ and the Last Judgment encourages believers to live in faith, obedience, and love, which are reflected in concrete actions and the formation of character in accordance with Christian values. Various theological views such as premillennialism, amillennialism, and postmillennialism provide different perspectives, yet all emphasize the importance of living with an orientation toward eternity. Amid the challenges of modern times, a proper understanding of eschatology becomes an important foundation so that believers are not trapped in fear or incorrect interpretations, but are instead able to use it as motivation to live morally, faithfully, and with hope. Therefore, the concept of the end times plays a significant role in shaping moral behavior that reflects a living faith and readiness to welcome eternal life.